2009
DOI: 10.1093/jmicro/dfp034
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of octacalcium phosphate in the dental calculus

Abstract: The purpose of this study was to morphologically demonstrate the presence of octacalcium phosphate in the dental calculus by judging from the crystal lattice image and its rapid transformation into apatite crystal, as part of our serial studies on biomineral products. We also aimed to confirm whether the physical properties of octacalcium phosphate are identical with those of the central dark lines observed in crystals of ordinary calcifying hard tissues. Electron micrographs showed that crystals of various si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…OCP is of a great biological importance because it is one of the stable components of human dental and urinary calculi (Chow and Eanes 2001;Kakei et al 2009). OCP was first proposed by W. E. Brown to participate as the initial phase in enamel mineral formation and bone formation through subsequent precipitation and stepwise hydrolysis of OCP (Brown 1962(Brown , 1966Brown et al 1962).…”
Section: Dcpa (Or Dcp)mentioning
confidence: 99%
See 1 more Smart Citation
“…OCP is of a great biological importance because it is one of the stable components of human dental and urinary calculi (Chow and Eanes 2001;Kakei et al 2009). OCP was first proposed by W. E. Brown to participate as the initial phase in enamel mineral formation and bone formation through subsequent precipitation and stepwise hydrolysis of OCP (Brown 1962(Brown , 1966Brown et al 1962).…”
Section: Dcpa (Or Dcp)mentioning
confidence: 99%
“…According to the data available (Poloni and Ward 2014), the unwanted depositions could consist of many substances and all of them always lead to various diseases. Regarding the unwanted depositions of CaPO 4 , they are found in soft tissue calcification (in damaged joints, blood vessels, dysfunctional areas in the brain, diseased organs, scleroderma, prostate stones) (Reid and Andersen 1993;Scotchford and Ali 1995;P'ng et al 2008;Brancaccio and Cozzolino 2005;Goff and Reichard 2006;Bittmann et al 2003;Molloy and McCarthy 2006;Giachelli 2004;Kazama et al 2007), kidney (Giannossi and Summa 2012;Mukherjee 2014) and urinary (Zhu et al 2014;Huo et al 2015;Selvaraju et al 2015) stones, dental pulp stones and dental calculus (Kakei et al 2009;Kodaka et al 1988Kodaka et al , 1998Ç iftçioglu et al 1998;Hayashizaki et al 2008), salivary stones (Zelentsov et al 2001;Luers et al 2014), gall stones (Qiao et al 2013;Hussain and AlJashamy 2013), pineal gland calcifications (Güney et al 2013), atherosclerotic arteries and veins (Ortlepp et al 2004;Tomazic 2001;Marra et al 2006;Kurabayashi 2013), coronary calcification (Fitzpatrick et al 2003;Matsui et al 2015), damaged cardiac valves (Suvorova and Buffat 2005), calcification on artificial heart valves (Giachelli 2001; Pettenazzo et al 2001;...…”
Section: Antlersmentioning
confidence: 99%
“…However, the development of both these types of crystals is not common in bone or in other normal calcified hard tissues. Given the assumption that either crystals with or without CDLs should be present, the difference in the ultrastructure of these 2 crystal types may indicate that a different mechanism is at work for the formation of apatite crystals 28,32) . In the case of dental calculus, we morphologically demonstrated that octacalcium phosphate (OCP) is involved in the formation of crystals without CDLs 32) .…”
Section: Discussionmentioning
confidence: 99%
“…Given the assumption that either crystals with or without CDLs should be present, the difference in the ultrastructure of these 2 crystal types may indicate that a different mechanism is at work for the formation of apatite crystals 28,32) . In the case of dental calculus, we morphologically demonstrated that octacalcium phosphate (OCP) is involved in the formation of crystals without CDLs 32) . Similarly, the appearance of crystals without CDLs may indicate the involvement of OCP in ectopic calcification, as has been pointed out by many researchers [33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation